2010
DOI: 10.1007/s00441-010-1010-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural evidence for human mast cell-eosinophil interactions in vitro

Abstract: We have hypothesized that mast cells (MC) and eosinophils (Eos), the main effectors of allergy, can form an effector unit. These cells co-exist in the inflamed tissues during the late and chronic stages of allergy and have been shown to be capable of influencing each other's survival and activity via soluble mediators. We have recently described couples of receptor-ligands that are expressed on either/both of these cells and that imply a physical interaction. In this study, we have investigated the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 47 publications
(54 reference statements)
2
39
1
2
Order By: Relevance
“…Recently, human cord blood-derived mast cells have been reported to contain LBs after in vitro differentiation and cultivation in the presence of 10% fetal bovine serum ( 33 ). Here, the mast cells were differentiated in serum-free medium, which contained 1% (140 M) fatty acid-containing BSA.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human cord blood-derived mast cells have been reported to contain LBs after in vitro differentiation and cultivation in the presence of 10% fetal bovine serum ( 33 ). Here, the mast cells were differentiated in serum-free medium, which contained 1% (140 M) fatty acid-containing BSA.…”
Section: Discussionmentioning
confidence: 99%
“…The eosinophil–mast-cell interaction was highlighted by a recent clinical study showing that in human patients with the allergic GI disorder EoE, eosinophils are physically coupled with mast cells as assessed by immunohistochemistry (84) and are a major source of the mast cell–supporting cytokine IL-9 (85). In vitro ultra-structural evidence also indicated that eosinophils and mast cells form cell-cell contact and exchange their products for reciprocal activation (84, 86). Importantly, anti–IL-5 therapy concomitantly reduced both eosinophils and mast cell numbers (84), indicating that eosinophils promote mastocytosis in human allergic disease.…”
Section: Eosinophils Directly Participate In Innate Recognition and Amentioning
confidence: 99%
“…As previously described [36], samples were washed twice with sodium cacodylate buffer (pH 7.4) and then postfixed with 1 % OsO 4 for 1 h at 4°C. Postfixed cells were dehydrated with a graded ethanol series ending with 100 % ethanol and then embedded in Dow Epoxy Resin (DER 332; Unione Chimica Europea, Milan, Italy) and DER732 (Serva, Heidelberg, Germany).…”
Section: Ultrastructural Analysis Of Mast Cell Phagocytosis and Subcementioning
confidence: 99%